2013
DOI: 10.11648/j.js.20130103.11
|View full text |Cite
|
Sign up to set email alerts
|

Negative Appendectomy Rate in Sultan Qaboos University Hospital, Oman

Abstract: Diagnosing acute appendicitis remains a challenge even with the presence of multiple diagnostic tools therefore, normal appendices are removed from some patients thought to have acute appendicitis. This is known as the negative appendectomy rate (NAR). The aim of this study was to find the rate of negative appendectomies in our institution among both adults and children and to analyze the characteristics of this group. The study included 654 patients who underwent appendectomies between January 2009 and Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In a study conducted in Oman, in line with this study, there were more boys than girls who had their appendix removed, and also the children under 12 years of age had a higher rate of unnecessary appendix removal compared to adults over 12 years. 35 In the study by Zouari et al, the average age of children who underwent appendectomy was reported to be 9 years. However, contrary to the current study, the rate of unnecessary appendix removal did not show a significant correlation with the gender of the children.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Oman, in line with this study, there were more boys than girls who had their appendix removed, and also the children under 12 years of age had a higher rate of unnecessary appendix removal compared to adults over 12 years. 35 In the study by Zouari et al, the average age of children who underwent appendectomy was reported to be 9 years. However, contrary to the current study, the rate of unnecessary appendix removal did not show a significant correlation with the gender of the children.…”
Section: Discussionmentioning
confidence: 99%
“…Certain countries like Oman in central Asia have reported a negative appendectomy rate of 12.23%. In the East Asia the negative appendectomy rate is about 18.2% as reported in Hong Kong [10][11][12][13].…”
Section: Negative Appendectomy Defini-tion and Ratementioning
confidence: 99%